O3-S3.06 Rescreening for chlamydial infection using home-based, self-obtained vaginal swabs: a randomised controlled trial in family planning clinic clients. (10th July 2011) - Xu, F; Stoner, B; Taylor, S; Mena, L; Tian, L; Papp, J; Hutchins, K; Martin, D; Markowitz, L
Abstract : Background: Family planning clinics provide contraceptive and preventive services for millions of low-income individuals. Screening and treatment for Chlamydia trachomatis infection in these clinics is a major part of the chlamydia control program in the USA. For women diagnosed with chlamydia, rescreening 3 months after treatment is recommended according to national guidelines. However, rescreening rates are low. The time and effort needed for patients to return to the clinic and the lack of access to follow-up care may contribute to the poor adherence to the rescreening recommendation. Methods: We conducted a randomised controlled trial in family planning clinics in three cities. After informed consent, women/girls >16 years treated for laboratory-confirmed chlamydial infection were randomly assigned to the Home Group (mailed a vaginal swab kit for self collection at home) or the Clinic Group (made a clinic appointment) for rescreening at 3 months following treatment. Reminder calls were made about 2 weeks before scheduled rescreening. The endpoint was rescreening within a 7 week window, 1 week before to 6 weeks after, the scheduled rescreening date. Results: 404 women were enrolled and their group assignments were randomised by opening centrally stuffed envelops. Women assigned to the Home Group had higher rescreening rate than those in the Clinic Group: Overall, 40.8% of 196 in the Home Group and 20.7% of 208 in the Clinic Group were rescreened (p<0.001). The rescreening rates were 38.4% (Home) vs 19.8% (Clinic) among those living with parents, and 48.2% (Home) vs 21.2% (Clinic) among those with a history of chlamydia infection prior to the treated episode at enrolment (both p<0.001). Among women reached by a reminder call, rescreening rates were significantly higher in the Home Group (59.2% of 130) than in the Clinic Group (37.8% of 111) (p<0.001). Among 163 women not reached by the reminder call, the rescreening rate were low (<5%) in both groups. In the Home Group, 12 tested positive for chlamydia compared to 8 in the Clinic Group, and the rate of reinfection was 12.9% in the Home Group and 14.6% in the Clinic Group (p=0.8). Conclusions: Use of home-based, self-obtained vaginal swabs resulted in a significant increase in rescreening rates compared to rescreening in the clinic. Our findings indicate a role for home-based specimen collection as an alternative to clinic-based rescreening for chlamydia in women.